DETERMINANT OF STOCK PRICE OF COAL MINING COMPANY LISTED ON INDONESIA STOCK EXCHANGE 2014-2018 - Nita Mayam Puspitasari; Suhendro; Rosa Nikmatul Fajri (Kusuma Negara Business School, 2020)
At present the capital market business is very promising. Stock investment is in great demand with the hope of getting capital gains or dividends so researchers want to know simultaneously and partially how the influence of Net Profit Margin (NPM), Return On Assets (ROA), Earning Per Share (EPS) and Dividend Per Share (DPS) on stock prices as respondents of Coal Mining companies listed on the Indonesia Stock Exchange in 2014-2018, there were 11 samples. The raw data from panel regression analysis is obtained from the financial statements (www.idx.com) so the simultaneous results of Net Profit Margin (NPM), Return On Assets (ROA), Earning Per Share (EPS) and Dividend Per Share (DPS) have an effect on stock prices. The Net Profit Margin (NPM) variable partially has a negative effect on stock prices. Variable Return On Assets (ROA, Earning Per Share (EPS) and Dividend Per Share (DPS) have no effect on stock prices. The coefficient of determination of 94% the rest is influenced by variables outside this observation.